Ruch Nowego Życia w Chinach, 1934–1948 - Demiańczuk, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In recent decades, there was a notable surge of interest in the history of the Republic of China (1912–1949). New Life Movement (Xin shenghuo yundong) was one of the most important endeavours undertaken during the so-called Nanjing Decade (1927–1937) — a period of authoritarian rule of Guomindang (National Party), after the triumph of the Northern Expedition and before the outbreak of the Second Sino-Japanese War. Inaugurated in 1934, this movement sought to revive Confucian virtues and create better society through the promotion of proper behaviour (especially etiquette and hygiene). Virtues, whose realisation in daily life was stated as the goal of the Movement, were li — propriety, yi — right action, lian — integrity, and chi — a sense of shame. Later, these goals were expanded to include promotion of militarisation (junshihua), aesthetic uplifting (yishuhua), and improving the production (shengchanhua) in peopleʼs lifestyles. Although the New Life Movement was initiated by Chiang Kai-shek on 19 February 1934 in Nanchang, in many respects it was a continuation of previous policies. To realise the New Life Movement, the Society for the Promotion of the New Life Movement (Xin shenghuo yundong cujin hui) was founded in 1934. Members of different factions in Guomindang participated in its activities. After the first two years, the New Life Movement disappeared from the spotlight, but remained active at least until 1948. During the war, the main task of the movement was participation in war efforts and, after the conflict ended, in post-war recovery. In the end, the New Life Movement failed in realisation of its stated goals. Nevertheless, it seems that its activities were still beneficial for Guomindang’s government. This article presents an outline of history and origins of the New Life Movement, as well as describe its goals and methods. In the end, there will be an evaluation of this important and controversial movement and its place in the history of Guomindang and China.
Keywords: authoritarianism; China; Confucianism; Chiang Kai-shek (1887-1975); Guomindang; New Life Movement; Republic of China